Teacher Motivation under Chhukha Dzongkhag - Dorji, Ten (International Journal of Humanities and Education Development (IJHED), 2024)
Teacher well-being and motivation play important roles in teacher and student experiences at school. When teachers fair well and are motivated to teach, they are more effective in their teaching. Fewer teachers leave the profession and they promote motivation and achievement among their students. This study investigated teacher motivation and factors affecting teachers’ motivation with the aim of advancing our understanding of the two constructs as well as finding out how they can be promoted among teachers. Study one involved motivation and testing of the attitude of teachers which measured 12 factors of teacher motivation and tested the attitude of teachers. Among a sample of 50 school teachers, results revealed that the new measure functioned similarly across the different demographic groups in the sample. The 12 factors of teacher motivational and testing of the attitude of teachers also revealed that attitude towards the profession is not that negative. Study two involved job satisfaction of teachers. The study on job satisfaction revealed that teachers in general are not satisfied with their profession. Study three involved examining importance of motivation. The findings showed that teachers’ motivation is the key to the success for student engagement and instructional strategies. Study four was associated with major motivational factors affecting teachers in schools. It presented that the motivation is the key to making teachers happy and do their best. Overall findings from the study revealed the significance of the basic psychological needs (autonomy, competence, and relatedness) in predicting teacher well-being and self-efficacy. Taken together, the four studies helped to improve our understanding of the important variables of teachers’ motivation. Implications of the findings for both research and practice are also discussed. For instance, major motivational factors like training opportunity, salary and perks, conducive working school environment and workload to mentioned a few, if taken care, will minimize the teacher attrition rate and will also address the issue of quality of education.